Komponen Pemasaran Teh Herbal Bukit Hexon pada PT. Karya Pak Oles Tokcer Denpasar Bali - STEVI VIONA LUMBANTORUAN; I WAYAN WIDYANTARA; PUTU UDAYANI WIJAYANTI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
Marketing component of Herbal Tea Bukit Hexon at PT. Karya Pak OlesTokcer Denpasar Bali Marketing is a combination of four variables that are the core of the company'smarketing system, consisting of product, price, place/distribution channels, andpromotions. This study is aimed at identifying the components of marketing carriedout by PT. Karya Pak Oles Tokcer and the constraints faced in marketing theirproducts. The research location was selected by purposive sampling. Types of datacollected included primary and secondary data. Data were collected by observation,interview, and documentation study. Data were analyzed descriptively andqualitatively. Based onthe results of research known component of the marketingdone by PT. By Pak Oles lessening of the products that the company provides onetype of packing to look more attractive in the eyes of connsumers, this type of use thepacking box. The selling price of tea sold is determined based on a calculation of rawmaterial usage, labor, production, operating costs and other costs. Based on theplace/distribution channels, herbal tea Bukit Hexon marketed through directmarketing distribution channel and indirectly. Promotional products are madethrough direct marketing activities (sales counter), sales promotion (rebates andbonuses) and advertising (flyers, newspaper and radio from the company it self).Constraints facing the company consists of internal and external constraints. Internalconstraints in terms of the promotion are less effective. External constraints in termsof competitors’ similar products. Suggested the company should use the print media,better known by the public such as the Bali Post and electronic media such as ads ontelevision so that are building relationships with the community and having apromotion more aggressively by opening a special stand tea sales as practiced bycompanies other tea products.